Insecticide physiological selectivity to Vespidae predators of Ascia monuste orseis - Crespo, André Luiz Barreto; Picanço, Marcelo Coutinho; Bacci, Leandro; Pereira, Eliseu José Guedes; Gonring, Alfredo Henrique Rocha (Pesquisa Agropecuaria Brasileira, 2002)
This work aimed to study the selectivity of the insecticides carbaryl, deltamethrin, methyl parathion, permethrin and trichlorfon in relation to Ascia monuste orseis (Godart) (Lepidoptera: Pieridae) and to their predators Brachygastra lecheguana Latreille and Protonectarina sylveirae (Saussure) (Hymenoptera: Vespidae). Based on concentration-response curves and lethal concentrations for 90% of the population (LC90), the differential selectivity index (DSI90), relative toxicity index and relative tolerance index (ReTI90) were calculated. Methyl parathion and trichlorfon were selective to B. lecheguana (DSI90 = 2.83 and 1.75) and P. sylveirae (DSI90 = 2.95 and 3.59) against A. monuste orseis. Deltamethrin and permethrin were selective to P. sylveirae (DSI90 = 1.98 and 2.70) against A. monuste orseis, but weren't selective to B. lecheguana (DSI90 = 0.21 and 0.64). B. lecheguana was less tolerant to deltamethrin, permethrin and trichlorfon than P. sylveirae (ReTI90 = 9.36, 4.23 and 2.05), but the opposite was observed to carbaryl (ReTI90 = 0.14). These two predators showed similar tolerance to methyl parathion (ReTI90 = 1.04). Concentration-response curves of carbaryl, permethrin and trichlorfon to both predators, deltamethrin to B. lecheguana, and methyl parathion to P. sylveirae, showed greater slopes than these curves to A. monuste orseis.
Keywords: Brachygastra lecheguana; Protonectarina sylveirae; insect control; biological control